Silver-Russell Syndrome and Cognitive Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Cognitive abilities of 20 boys and 5 girls, aged 6 to 11 years, with Silver-Russell syndrome were investigated at the Prince of Wales Hospital, Shatin, Hong Kong, the Institute of Child Health, and Middlesex Hospital, London, UK.